2015
DOI: 10.2174/1874285801509010018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antimicrobial Activity of Few Saudi Arabian Snake Venoms

Abstract: BackgroundVenoms of two cobras, four vipers, a standard antibiotic and an antimycotic, were evaluated comparatively, as antimicrobials.Methods:Six venom concentrations and three of the standard antibiotic and the antimycotic were run in micro-dilution and diffusion plates against the microorganisms.RESULTS: Echis pyramidum, Echis coloratus and Cerastes cerastes gasperettii highest venom concentrations gave significant growth inhibition zones (GIZ) with respect to a negative control, except Bitis arietans, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
(30 reference statements)
0
7
1
Order By: Relevance
“…Except for 10 µg/mL NMV-induced G1 cell cycle arrest of C. glabrata , the effects were relatively slight ( Figure 2 b). As mentioned above, data on crude cobra venom-related effects on fungal cell growth and cell cycle progression are limited [ 24 ]. More recently, cardiotoxin 1 (CTX-1), a component of the venom of the Chinese cobra Naja atra , has been shown to be active against several unicellular fungal species, namely C. albicans , C. glabrata and Malassezia pachydermatis (minimal fungicidal concentration (MFC) ranging from 6.3 to 50 μg/mL) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for 10 µg/mL NMV-induced G1 cell cycle arrest of C. glabrata , the effects were relatively slight ( Figure 2 b). As mentioned above, data on crude cobra venom-related effects on fungal cell growth and cell cycle progression are limited [ 24 ]. More recently, cardiotoxin 1 (CTX-1), a component of the venom of the Chinese cobra Naja atra , has been shown to be active against several unicellular fungal species, namely C. albicans , C. glabrata and Malassezia pachydermatis (minimal fungicidal concentration (MFC) ranging from 6.3 to 50 μg/mL) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, antifungal properties of snake venoms are much less studied and the research is focused mainly on the biological activities of venoms of viperid species (Viperidae family) [20][21][22][23]. In contrast, the antifungal activity of the venoms of elapid species (Elapidae family) is less evident [24,25]. For example, it has been reported that the venoms of two cobras, namely Walterinnesia aegyptia and Naja haje arabica, have no antimycotic activity against the human fungal pathogen C. albicans based on zone of growth inhibition assay [24].…”
Section: Npv-and Nmv-mediated Changes In Cell Viability Cell Cycle Amentioning
confidence: 99%
See 1 more Smart Citation
“…Bactericidal activity against Gram-positive and Gram-negative bacteria was attributed to various components, including L-amino acid oxidases and phospholipase A2 enzymes. [22][23][24][25][26][27] However, these bactericidal effects are likely to decrease once the venom has been injected. Soft tissue infection occurs in patients suffering severe envenomings (grade 3 or 4) in which the injected venom amount is likely to be high.…”
Section: Discussionmentioning
confidence: 99%
“…The non-toxins in snake venom have some pharmacological properties, including anticancer properties, antimicrobial properties, and analgesic properties [13,14]. Although it is a fact that the nontoxic protein in snake venom possesses antimicrobial potentials, no or scanty literature exists showing the efficacy of this venom as an alternative to metronidazole in the eradication of T. vaginalis [15].…”
Section: Introductionmentioning
confidence: 99%